Bacterial small RNAs may mediate immune response differences seen in respiratory syncytial virus versus rhinovirus bronchiolitis - Krohmaly, Kylie I.; Perez-Losada, Marcos; Ramos-Tapia, Ignacio; Zhu, Zhaozhong; Hasegawa, Kohei; Camargo Jr., Carlos A.; Harmon, Brennan; Espinola, Janice A.; Reck Cechinel, Laura; Batabyal, Rachael; Freishtat, Robert J.; Hahn, Andrea (Frontiers in Immunology, 2024)
Bronchiolitis, a viral lower respiratory infection, is the leading cause of infant hospitalization, which is associated with an increased risk for developing asthma later in life. Bronchiolitis can be caused by several respiratory viruses, such as respiratory syncytial virus (RSV), rhinovirus (RV), and others. It can also be caused by a solo infection (e.g., RSV-or RV-only bronchiolitis) or co-infection with two or more viruses. Studies have shown viral etiology-related differences between RSV-and RV-only bronchiolitis in the immune response, human microRNA (miRNA) profiles, and dominance of certain airway microbiome constituents. Here, we identified bacterial small RNAs (sRNAs), the prokaryotic equivalent to eukaryotic miRNAs, that differ between infants of the 35 th Multicenter Airway Research Collaboration (MARC-35) cohort with RSV-versus RV-only bronchiolitis. We first derived reference sRNA datasets from cultures of four bacteria known to be associated with bronchiolitis (i.e., Haemophilus influenzae, Moraxella catarrhalis, Moraxella nonliquefaciens, and Streptococcus pneumoniae). Using these reference sRNA datasets, we found several sRNAs associated with RSV-and RV-only bronchiolitis in our human nasal RNA-Seq MARC-35 data. We also determined potential human transcript targets of the bacterial sRNAs and compared expression of the sRNAs between RSV-and RV-only cases. sRNAs are known to downregulate their mRNA target, we found that, compared to those associated with RV-only bronchiolitis, sRNAs associated with RSV-only bronchiolitis may relatively activate the IL-6 and IL-8 pathways and relatively inhibit the IL-17A pathway. These data support that bacteria may be contributing to inflammation differences seen in RSV-and RV-only bronchiolitis, and for the first time indicate that the potential mechanism in doing so may be through bacterial sRNAs.